Avaliação de um ELISA competitivo para detecção de anticorpos contra Babesia bovis - Götze, Marcelo Mendes (2010)
Bovine babesiosis caused by Babesia bovis and Babesia bigemina, is the most important disease transmitted by Rhipicephalus (Boophilus) microplus in tropical and subtropical areas in South America. Definitive diagnosis can be made by detecting infected erythrocytes in blood smears. However, the parasitemia in peripheral blood is often too low for this method to be used for diagnostic purposes. For this reason, several serological tests, including complement fixation, indirect hemagglutination and indirect immunofluorescence (IIF) have been used to detect antibodies in infected cattle. Although these tests allow the detection of persistently infected animals, they have limitations in specificity and/or sensitivity. The IIF has been the most sensitive, but cross-reactivity between species, subjective interpretation, and low production has limited its usefulness. The enzyme linked immunosorbent assay (ELISA) have found wide application in the diagnosis of infectious diseases. The cELISA format (competitive) can provide an additional level of specificity, because the antibody is directed to a single epitope, specific for the organism to be detected. For these reasons, this study aimed to evaluate the sensitivity and specificity of cELISA compared to IIF and nested PCR (nPCR) for diagnosis babesiosis caused by B. bovis. Therefore, blood samples were collected from cattle in Brazil and Argentina, and processed for the diagnosis of B. bovis. The nPCR was used as the gold standard to validate the cELISA and the IIF as a comparative test. The cELISA for the diagnosis of B. bovis presented is easily processed with high levels of sensitivity and specificity. It is easily performed in a high number of samples, making it useful in cases of outbreaks of bovine babesiosis.